Prognosis in HR-positive metastatic breast cancer with HER2-low versus HER2-zero treated with CDK4/6 inhibitor and endocrine therapy: a meta-analysis - Lin-Yu Xia; Xu-Chen Cao; Qing-Lin Hu; Wei-Yun Xu (Frontiers in Oncology, 2024)
BackgroundThe combination of CDK4/6 inhibitors (CDK4/6i) and endocrine therapy (ET) is currently the standard first-line treatment for patients with metastatic hormone receptor positive (HR+), and HER2-negative (HER2-) breast cancer. However, the impact of HER2 status on the prognosis of patients receiving CDK4/6i and ET remains unclear. The meta-analysis was conducted to evaluate different outcomes between HER2-low and HER2-zero patients in advanced HR+ breast cancer receiving CDK4/6i and ET.MethodsA systematic search was performed in PubMed and EMBASE databases for relevant published literature. Objective response rate (ORR), overall survival (OS), and progression-free survival (PFS) were pooled by fixed or random effects models.ResultsOverall, 12 studies with 3567 patients were eligible for analysis. The pooled analysis suggested that no significant differences were observed in terms of ORR and OS between HER2-low and HER2-zero patients who underwent CDK4/6i and ET. Similarly, no significant difference in PFS was found between HER2-low and HER2-zero patients who underwent post-line CDK4/6i and ET or first-line Palbociclib and ET. However, in patients who received mixed-line (not a single treatment line) or first-line CDK4/6i and ET, the PFS was significantly shorter in the HER2-low subgroup than in the HER2-zero subgroup (mixed-line: HR = 1.36; 95% CI = 1.11–1.65; P = 0.002; first-line: HR = 1.14; 95% CI = 1.01–1.28; P = 0.04). A similar phenomenon was observed in patients who received mixed-line or post-line Palbociclib and ET (mixed-line: HR = 1.60; 95% CI = 1.09–2.34; P = 0.02; post-line: HR = 1.43; 95% CI = 1.03–2.00; P = 0.03).ConclusionThese results indicated that HER2-low status did not have a significant association with ORR and OS, but it may have a worse impact on PFS in patients who received mixed-line or first-line CDK4/6i and ET, as well as mixed-line or post-line palbociclib plus ET.